Evaluating four nitrous oxide emission algorithms in response to N rate on an irrigated corn field. (October 2015) - Fang, Q.X.; Ma, L.; Halvorson, A.D.; Malone, R.W.; Ahuja, L.R.; Del Grosso, S.J.; Hatfield, J.L.
Abstract: In this study, the RZWQM2 (Root Zone Water Quality Model) was used to simulate the responses of N2 O emissions to different Nitrogen application rates on an irrigated corn field from 2003 to 2006, in eastern Colorado, USA. Four different algorithms from the literature were coupled with RZWQM2 and compared for simulating N2 O emissions during nitrification and denitrification processes. The RZWQM2 was first calibrated for corn yield, N uptake, soil water (0–10 cm) and soil Nitrate-N content (0–180 cm) and the simulated daily nitrification and denitrification rates were used to calculate N2 O emission using the algorithms from DAYCENT, NOE (Nitrous Oxide Emissions), WNMM (Water and Nitrogen Management Model), and FASSET models. The best N2 O emission was simulated when the fraction of N2 O release from nitrification was modified by water filled pore space (WFPS) as in the NOE model and the fraction N2 O release from denitrification was adopted from the DAYCENT model. Highlights: This research compared four different greenhouse gas emission algorithms in RZWQM2. The best algorithm is now implemented in RZWQM2. The new model showed adequate responses of N2 O emission to fertilizer rate in a corn field.